Expression of bcr and bcr-abl fusion transcripts in normal and leukemic cells. - Collins, S (Mol Cell Biol, 1987)
The translocation of the c-abl oncogene from chromosome 9 to the bcr gene on chromosome 22 in cases of Philadelphia chromosome-positive chronic myelogenous leukemia (CML) generates an aberrant bcr-abl fusion transcript which may be intimately related to the pathogenesis of CML. Because factors controlling normal bcr expression might also be involved in the expression of this aberrant bcr-abl transcript, we studied the patterns of expression of the normal bcr gene in different cell types. We found that the normal bcr gene was expressed in many different types of human cells. Moreover, the bcr gene was evolutionarily conserved, and homologous bcr genomic sequences and RNA transcripts were readily detected in chick tissue. The highest level of bcr expression in chick tissue was in brain tissue, the lowest level was in liver tissue, and a truncated bcr mRNA was noted in chick testes. Normal bcr transcripts, in addition to the aberrant bcr-abl hybrid transcripts, have been found in all Philadelphia chromosome-positive CML cells studied to date. Within a given CML sample, the relative amounts of normal bcr RNA and aberrant bcr-abl RNA were similar. In addition, the normal bcr and the aberrant bcr-abl hybrid transcripts demonstrated similarly prolonged half-lives compared with that of the normal abl-related transcripts in CML cells. These findings suggest that in CML cells, similar cellular mechanisms control the steady-state levels of both the normal bcr and the bcr-abl fusion RNAs. IMAGES: